Wagnerian trees and forests - Jovells Argelich, Ramón (Escritura e Imagen, 2019)
In this article you can see a small sample of the importance of nature in the work of Richard Wagner (1813-1833). These Wagnerian works are entwined with ancient traditions of the first settlers of northern Europe in which it is worth highlighting their beliefs, rituals and traditions, all of them very attached to the territory, its orography and its nature. In particular, trees and forests are referred to. These living beings who are anchored in the territory are recognized and respected. With its Mayan presence and its large dimensions are elements that surprise and captivate man from the past. Of these living beings must also be highlighted its mysterious environment. This environment is formed with elements of magical, sacred meanings, and in turn, revered by different settlers over time. This article aims to visualize the strength and atmosphere of these tree and wooded elements within the Wagnerian scene.
Keywords: To be human; nature; tree; forest; metamorphosis; mystery; sacred; strength